Perspectives of social entrepreneurship in Portugal: comparison and contrast with international theoretical approaches - Parente, C. (2017)
The aim of this article is to present and discuss the perspectives of social entrepreneurship conveyed by third sector organizations in Portugal in the context of the main international theoretical approaches. As part of a research project on social entrepreneurship in Portugal, the article analyses the content of 20 semi-structured interviews with key actors within the Portuguese third sector. It is assumed that the roles these actors play are a clear indicator of the importance their views can hold in defining the social entrepreneurship field in Portugal. This analysis enables us to conclude that heterogeneous views and blurred defined boundaries frame the debate on social entrepreneurship’s processes and definitions, with some actors even rejecting it in favour of other concepts such as “social economy” or “solidarity economy”. Nevertheless, the central issues that arose are associated with the individual qualities of the entrepreneur, as well as the sustainability of the initiatives.